Expectations about the success of treatment for addiction to psychotropic drugs in the view of specialists (Research, Society and Development, 2021)
This study aimed to understand how specialists, scholars of psychoactive substance dependence, consider the success of a treatment of this problem, taking into account their experiences and their different approaches to the subject in Brazil. The bases of qualitative methodology were used. The construction of the sample was based on the principle of intentional sampling; an electronic questionnaire on the Monkey Survey platform was used as a tool for this research; the recruitment of PhD academics was done using CNPq's Lattes platform. The process of analyzing the results followed the premises of Content Analysis: thus, the material enabled the construction of a thematic area and from the grouping of this information, categories for analysis were constructed. Thus, 464 emails were sent, and 55 participants were considered, 5 categories were found (Change in consumption pattern; Quality of Life; Social Reinsertion; Emotional Development; Autonomy). The analysis showed that specialists have very audacious expectations, such as: abstinence, independence in conducting their own lives, returning to work and study activities, reactivating relationships with family and friends. These expectations are difficult to reach, since other variables that interfere in their realization are ignored, such as: prejudice and society's rejection of substance users, unfriendly family, vulnerable situations, etc. This situation can hinder the treatment process of individuals affected by the problem of substance dependence.